Artificial Intelligence and Socio-Scientific Controversies in Science Teaching in Higher Education. Approaches and Projections Based on a Bibliographic Review - Joglar-Campos, C; González-Sepúlveda, R; González-Sepúlveda, R (INST EDUCACAO UNIV LISBOA, 2025)
This literature review explores the implementation of Artificial Intelligence (AI) and Natural Language Processing (NLP) in the analysis of student feedback in universities. The methodology includes identification of the topic, systematic search of sources, assessment of the relevance and quality of the studies, and synthesis of the findings. The advantages and challenges of using AI and NLP to analyse student feedback, as well as their impact on improving educational quality, are discussed. The case studies of this literature review provide valuable information for the integration of socio-scientific controversies (SSC) in science education.